Structure and composition of native tree species in Taratibu in Quirimbas National Park (Research, Society and Development, 2023)
The analysis of the structure of a forest allows making deductions about the origin, ecological characteristics, dynamics and trends of its future development and fundamental information to subsidize conservation strategies. The objective of this research was to evaluate the horizontal structure and floristic composition of a forest located in the Quirimbas National Park (PNQ), northern Mozambique. For this purpose, 32 plots of 50x20m were systematically allocated, within which the height and DBH of all tree individuals with DBH ≥ 10 cm were measured. The floristic composition was also evaluated, based on the distribution of individuals identified by species, genus and botanical family, and the structure of the forest, based on the analysis of phytosociological parameters, species diversity and diametric structure. A total of 772 individuals belonging to 32 species, 27 genera and 11 families were identified, with the Fabaceae family being the most dominant with 44% of the species, followed by Combretaceae (13%) and Euphorbiaceae (9%). The most important species, according to the Importance Value Index (IVI) were Julbernardia globiflora (19.92%), Pteleopsis myrtifolia (8.55%) Burkea africana (7.82%), Combretum apendiculatum (7.77%) , Diplorhynchus condylocarpon (7.30%) and Dalbergia melanoxylon (7.06%). The species diversity measured by the Shannon Winner index (H´) was 1.69. The diameter structure followed the traditional inverted-j trend, however with slight variation in the 17.5 cm and 42.5 cm classes, proving that the forest structure of the Taratibu reserve still has good ecological stability.